The effect of Suggested Learning Curriculum to develop some of the Perceptual – Motor Abilities for the students of the Institutes - Kamal, Waleed (Journal of Physical Education, 2012)
The Contribution to the absorption of the learner and the acquisition of habits and motor abilities in many activities that need to estimate the spatial relations and compliance and that any weakness in this capacity reduces the effectiveness of learning and thus lead to motor behavior is integrated. So study aimed to develop a curriculum and knowledge of their impact on the development of some of the capacity of perception - motor.The researcher has used the experimental method and included a sample search on (30 students) of the first phase of the Institute of Physical Education in Khanaqin, were divided into two groups of equal number and randomly, has been applied to the curriculum proposed for the experimental group for a period (8 weeks) at a rate of two teaching hospitals in the week. Has been reached that the proposed curriculum using tools and equipment and the various positions have had a positive effect in the kinetic gain experience and thus develop the capacity of perception - motor for students of institutes of physical education as well as their positive impact in learning motor skills of various sports .